2015
DOI: 10.3329/dujps.v12i2.21981
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric analysis of Azithromycin and its pharmaceutical dosage forms: Comparison between Spectrophotometry and HPLC

Abstract: A simple, reliable, precise and sensitive UV-spectrophotometric method was developed and validated for the estimation of azithromycin in pharmaceutical dosage form and compared with official USP 2010 method. The proposed method utilizes the oxidation of azithromycin with potassium permanganate to liberate formaldehyde. This formaldehyde reacts with acetone-ammonium reagent and produces yellow colored chromogen 3,5-diacetyl-2,6-dihydrolutidine. The colored solution exhibited a maximum absorption at 412 nm which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Because of the low release profiles(brand A2), local sources may need to improve some practices, and regulatory authorities may need to increase monitoring of the quality of pharmaceutical products manufactured by local industries. Similar results were reported from India [ 6 ], and Bangladesh [ 58 ]. However, the dissolution result of the finding different from the study done in Belgium [ 18 ], and Cameroon [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Because of the low release profiles(brand A2), local sources may need to improve some practices, and regulatory authorities may need to increase monitoring of the quality of pharmaceutical products manufactured by local industries. Similar results were reported from India [ 6 ], and Bangladesh [ 58 ]. However, the dissolution result of the finding different from the study done in Belgium [ 18 ], and Cameroon [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…There is a need to analyze pharmaceutical formulations of AZM qualitatively and quantitatively. The absorption of AZM in raw materials, biological samples, and pharmaceutical formulations is determined by many techniques, such as high-performance liquid chromatography (HPLC), , mass spectrometry (MS), Fourier transform infrared spectroscopy, UV–vis spectroscopy, LC–MS, and electrochemical methods. , All above mentioned methods have some limitations such as being inflated, time-consuming, requiring rigorous sample preparation, and being laborious. In comparison to UV–vis spectrometry, Raman scattering is preferable as it is perceived in a single-beam mode which uses no reference channel to minimize instrumental sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…1). Literature reveals few spectrophotometric methods [18][19][20][21][22][23] and two fluorimetric assays [24,25] for determination of AZN in bulk and formulations. A detailed review for RSGL estimation [26] is reported, without direct fluorimetric technique.…”
mentioning
confidence: 99%